The Effect of the Addition of Turbo cyclone on the Inlet Air on Torque and Power in the Toyota Avanza 1300 CC - Ilham Zikri; Remon Lapisa (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2021)
The decrease in the performance of the vehicle is influenced by several factors such as low air pressure entering the throttle body . The purpose of this research is to improve vehicle performance again. This study used an experimental method conducted at the UNP Automotive Engineering Vehicle Testing Workshop using a Toyota Avanza 1300 CC vehicle, power and torque research was carried out by adding a turbo cyclone. Research data collection was carried out three times in each test. The results of research that has been carried out on the Toyota Avanza 1300 CC vehicle. 1) Installation of a turbo cyclone at a slope of 55o is the biggest increase in power, which is 3.3 Kw / 4.422 Hp. 2) Installation of a turbo cyclone at a slope of 65o, the largest increase in torque, which is 7.3 Nm. From the use of a turbo cylone so as to make air pressure increase, it affects torque and power. Penurunan kinerja dari kendaraan dipengaruhi beberapa faktor seperti rendahnya tekanan udara yang masuk kedalam throttle body . Tujuan penelitian ini untuk meningkatkan kembali performa kendaraan. Penelitian ini menggunakan metode eksperimen yang dilakukan di Workshop Pengujian Kendaraan Teknik Otomotif UNP dengan menggunakan kendaraan Toyota Avanza 1300 CC, penelitian daya dan torsi dilakukan dengan menambahkan turbo cyclone. Pengambilan data penelitian dilakukan tiga kali pada tiap pengujian. Hasil penelitian yang telah dilakukan pada kendaraan Toyota Avanza 1300 CC. 1) Pemasangan turbo cyclone pada kemiringan 55o, menjadi peningkatan daya paling besar yaitu sebesar 3,3 Kw / 4,422 Hp. 2) Pemasangan turbo cyclone pada kemiringan 65o, menjadi peningkatan torsi paling besar yaitu sebesar 7,3 Nm. Dari penggunaan turbo cylone sehingga membuat tekanan udara meningkat mempengaruhi torsi dan daya.